Spatial and Temporal Variations of Erosion and Accretion: A Case of a Large Tropical River - Saleem, Ashty; Dewan, Ashraf; Rahman, M.M.; Nawfee, S.M.; Karim, R.; Lu, X.X. (2019)
Rapidly changing river systems can impact people, property and infrastructures. This study investigates bank erosion and accretion of the Padma River in Bangladesh, through space and time, using historical topographic maps, Corona and Landsat images and navigational charts. A geographic information system (GIS) was utilised to quantify the erosion and accretion pattern. In addition, volumetric changes in the riverbed were also investigated. Results indicated that the area of erosion and deposition vary both spatially and temporally. However, erosion was more prominent on the left bank, whilst accretion was high along the right bank, over the study period. Overall, average annual erosion rates were higher than accretion rates (17 km2 year−1 versus 13 km2 year−1). The volumes of morphological change for two epochs correspond to a net volume gain of 338.75 million m3 sediment between 1984 and 1992 but a net loss of 295.20 million m3 during the period 1992–2008. Regression analysis between bank erosion and mean annual flow, peak discharge and mean flood flow showed that two of the three independent variables were significantly associated with bank erosion. The area of large mid-channel bars increased over time, which may have had a role in shaping erosion and accretion processes of the river. As increased runoff is expected in the future, as a result of enhanced rainfall under warmer climate, knowledge of this work will help to determine the morphological response of fluvial systems in Bangladesh and elsewhere.